Crystallization of citrate-stabilized amorphous calcium phosphate to nanocrystalline apatite: a surface-mediated transformation. Issue 18 (15th April 2016) - Chatzipanagis, Konstantinos; Iafisco, Michele; Roncal-Herrero, Teresa; Bilton, Matthew; Tampieri, Anna; Kröger, Roland; Delgado-López, José Manuel
Abstract : The mechanisms underlying the crystallization of cit-ACP in two relevant media have been explored by combining in situ Raman spectroscopy and ex situ TEM. Citrate desorption from cit-ACP triggers the surface-mediated crystallization to nanocrystalline apatite. Abstract : This work explores the mechanisms underlying the crystallization of citrate-functionalized amorphous calcium phosphate (cit-ACP) in two relevant media, combining in situ and ex situ characterization techniques. Results demonstrate that citrate desorption from cit-ACP triggers the surface-mediated transformation to nanocrystalline apatite (Ap). Our findings shed light on the key role of citrate, an important component of bone organic matrix, and the medium composition in controlling the rate of transformation and the morphology of the resulting Ap phase.